2021
DOI: 10.1080/20008198.2021.1888525
|View full text |Cite
|
Sign up to set email alerts
|

Validation of posttraumatic stress disorder (PTSD) and complex PTSD in Chinese children as per the ICD-11 proposals using the International trauma questionnaire

Abstract: Background : Given that the validity of applying complex posttraumatic stress disorder (CPTSD) in nonclinical children remains unclear. Objectives : The current study aimed to explore the factor structure, discriminant validity, and risk factors of ICD-11 posttraumatic stress disorder (PTSD) and CPTSD using the International Trauma Questionnaire. Methods : A total of 3478 trauma-exposed Chinese children aged 9–12 years were included in this study. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
2
12
1
Order By: Relevance
“…Consistent with prior studies where sexual trauma was identified as a predominant risk factor for CPTSD, 19,21,72,73 experiences of sexual trauma at lower and higher frequencies of exposure significantly predicted 'CPTSD class' membership. Notably, sexual trauma was also a risk-factor for 'DSO class's membership, 74 although this effect was applicable only at lower quantities of exposure. It is likely that DSO symptoms resonate strongly with victims of sexual trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies where sexual trauma was identified as a predominant risk factor for CPTSD, 19,21,72,73 experiences of sexual trauma at lower and higher frequencies of exposure significantly predicted 'CPTSD class' membership. Notably, sexual trauma was also a risk-factor for 'DSO class's membership, 74 although this effect was applicable only at lower quantities of exposure. It is likely that DSO symptoms resonate strongly with victims of sexual trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior studies demonstrating the second-order model provides a better representation of data sampled from clinical or highly traumatized adult populations using the ITQ [ 4 , 9 ], and in trauma-exposed foster children using the ITQ-CA [ 12 , 14 ]. Conversely, a study of trauma-exposed Chinese children sampled from the general population demonstrated the correlated six-factor model provided the best fit, but this study used the adult version of the ITQ [ 13 ]. Therefore, more research is needed to clarify the factorial structure of the ITQ-CA in assessing ICD-11 CPTSD in Chinese populations across different settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of trauma-exposed adolescents in the general population in Lithuania also support the factorial validity of ICD-11 CPTSD using the ITQ-CA [ 17 ], and found family problems, school problems, and lack of social support as factors that differentially predicted PTSD versus CPTSD [ 18 ]. Although two recent studies of trauma-exposed adolescents in Mainland China also support the factorial validity of ICD-11 CPTSD and identified distinct symptom profiles of PTSD and CPTSD [ 13 , 19 ], these studies were limited by the use of the adult version of the ITQ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brewin et al ( 17 ) further suggest that the value of ICD-11 is that it provides a brief set of systems to distinguish between two sibling disorders, PTSD and complex PTSD (CPTSD). Several studies examine the association of PTSD with disasters, such as studies of earthquake survivors in China ( 19 , 20 ), Australian accident victims ( 21 ), and preadolescent children exposed to a hurricane in the United States ( 22 ). The findings of these studies indicate that the ICD-11 model has an acceptable fit for data collected from postdisaster settings.…”
Section: Introductionmentioning
confidence: 99%